Function of Wildfire-Deposited Pyrogenic Carbon in Terrestrial Ecosystems - Pingree, Melissa R. A.; DeLuca, Thomas H. (Frontiers in Environmental Science, 2017)
Fire is an important driver of change in most forest, savannah, and prairie ecosystems and fire-altered organic matter, or pyrogenic carbon (PyC), conveys numerous functions in soils of fire maintained terrestrial ecosystems. Although an exceptional number of recent review articles and books have addressed agricultural soil application of charcoal or biochar, few reviews have addressed the functional role of naturally formed PyC in fire maintained ecosystems. Recent advances in molecular spectroscopic techniques have helped strengthen our understanding of PyC as a ubiquitous, complex material that is capable of altering soil chemical, physical, and biological properties and processes. The uniquely recalcitrant nature of PyC in soils is partly a result of its stable C=C double bonded, graphene-like structure and C-rich, N-poor composition. This attribute allows it to persist in soils for hundreds to thousands of years and represent net ecosystem C sequestration in fire maintained ecosystems. The rapid formation of PyC during wildfire or anthropogenic fire events short circuits the normally tortuous pathway of recalcitrant soil C formation. Existing literature also suggests that PyC provides an essential role in the cycling of certain nutrients, greatly extending the timeframe by which fires influence soil processes, and facilitating recovery in ecosystems where organic matter inputs are low and post-fire surface soil bacterial and fungal activity is reduced. The high surface area of PyC allows for the adsorption a broad spectrum of organic compounds that directly or indirectly influence microbial processes after fire events. Adsorption capacity and microsite conditions created by PyC yields a ‘charosphere’ effect with heightened microbial activity in the vicinity of PyC. In this mini-review, we explore the function of PyC in natural and semi-natural settings, provide a mechanistic approach to understanding these functions, and examine examples of such mechanisms in published literature.